CONDUCTING GESTURE AS A MEANS OF MUSICAL EXPRESSION IN CHORAL PERFORMANCE (Scientific journal of the Fergana State University, 2026)
The article examines the role of the conductor's gesture as a fundamental means of non-verbal communication between the conductor and the choral ensemble. Based on many years of practical and pedagogical experience, the study emphasizes the semiotic, psychological, and methodological aspects of choral conducting. Specific examples from educational and concert practice are provided, revealing the mechanisms by which gestures influence intonational accuracy, ensemble tuning, and artistic expressiveness of performance.